123k views
1 vote
Determine where the points above end up after each transformation.

Determine where the points above end up after each transformation.-example-1

1 Answer

2 votes

\begin{gathered} \text{parent function is y=k(x)} \\ \text{this is transformed to y=2k(-x)} \\ \\ \end{gathered}
\begin{gathered} \text{hence,} \\ x\text{ goes to -x} \\ \text{and} \\ y\text{ goes to 2y} \\ \text{this implies that} \\ (-2,-1)\text{ }\Rightarrow(2,2k(2)) \\ (-1,2)\Rightarrow(1,2k(1)) \\ (3,1)\Rightarrow(-3,2k(-3)) \\ \text{therefore} \\ (-2,-1)\text{ }\Rightarrow(2,-2) \\ (-1,2)\Rightarrow(1,4) \\ (3,1)\Rightarrow(-3,2) \end{gathered}

User Kenju
by
5.3k points